Cognitive Appraisal Role in Relationship between Psychological Capital and Metacognitive Beliefs by Distress Tolerance - Fatameh Zanganeh Parsa,; Hobbi, Mohammadbagher (International Journal of Psychosocial Rehabilitation, 2020)
This paper aimed to model the role of negative cognitive appraisal in relationship between distress tolerance with psychological capital and negative metacognitive beliefs in couples suffering from infidelity. The present research method was a path analysis study with the correlation design of structural equations. 400 person were selected by Convenience sampling method from Tehranian married men and women suffering from infidelity that who referred to family counseling centers in the middle of 2019. Data collection was performed using questionnaire and were analyzed by AMOS and Spss22 software. The results showed that the designed model to explain the distress tolerance according to role of cognitive appraisal, had acceptable fitness indicators. Accordingly, the relationship between psychological capital and negative metacognitive beliefs variables by distress tolerance was confirmed through cognitive appraisal of stress. Thus, the variable of stress cognitive appraisal showed a moderating or decreasing role. That is, it facilitates the role of negative metacognitive beliefs in distress tolerance. Furthermore, the high negative cognitive appraisal of stress moderates the role of psychological capital on distress tolerance. According to the results, it can be said that various factors such as stress assessment play an important role in explaining the distress tolerance in couples suffering from infidelity.